Tongass odyssey : seeing the forest ecosystem through the politics of trees : a biologist's memoir - Schoen, John W. (University of Alaska Press, 2020)
"John Schoen's Tongass Odyssey is both a memoir and a scientific manuscript. As a memoir it offers authorial stories related to Schoen's dealings in the Tongass National Forest; as a science-based manuscript it addresses the ecological and political history of the past 50 years of the Tongass. It also addresses the responsibility of conservation practitioners regarding the consequences of public lands and water management"--